The growth characteristics of sparid otoliths - Lang, Judy Brenda (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1992)
The periodicity of formation of growth increments in the otoliths of South African sparids was validated by the oxytetracycline labelling technique. Intramuscular injections of oxytetracycline at a dosage of 250mg/kg marked the otoliths of laboratory held juvenile sparids, while a dosage range of 50 - 100mg/kg oxytetracycline, injected intramuscularly, marked adult sparids in the field. Laboratory held, larval sparid otoliths were marked by immersion for 24hrs a solution of 100-150mg/l alizarin complexone. Both daily (microstructural) and annual (macrostructural) growth increments were identified in the otoliths. The micro incremental pattern of deposition in the sparid otoliths conformed to the general pattern of otolith structure. Sparid otoliths consisted of a central opaque nucleus composed of multiple primordia. surrounding this nucleus were daily increments which decreased in width as the distance from the nucleus increased. Both check rings and subdaily increments were visible throughout the otolith. Minor environmental changes did not affect micro incremental deposition. Narrow opaque and wide hyaline annual growth zones were identified in sectioned sparid otoliths. Scanning electron microscope analysis of the annual growth zones revealed that microincrements within the opaque zone were narrowly spaced with prominent discontinuous phases. This resulted in the greater optical density and higher protein content of the zone. The hyaline zone was composed of widely spaced daily increments with prominent incremental phases accounting for the translucent nature of this zone. Opaque zone formation in the otoliths of many South African sparids was found to occur primarily during periods of reproductive activity and was shown to be indicative of slow otolith growth. The hyaline zone was formed after the spawning season, representative of fast otolith growth. The results of this study have resolved much of the controversy surrounding the rate of growth and time of formation of the opaque and hyaline growth zones in South African sparid otoliths.
Keywords: Fishes -- Age determination; Otoliths; Sparidae